2019
DOI: 10.4028/www.scientific.net/msf.947.109
|View full text |Cite
|
Sign up to set email alerts
|

Assistive Electro Discharge Machining of AIN Ceramics

Abstract: Electro discharge machining process experiences limitation due to the non-conductive nature of the workpiece material. However, researchers proposed assistive EDM technique to machine nonconductive materials in the past. These assistive techniques require a minimal thickness of 100 µm conductive coating on the workpiece surface which usually takes longer time to coat the surface using PVD (physical vapor deposition) method. In this paper, a new modified assistive EDM method has been proposed to machine noncond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The preparation time for the new coating was an hour and the experimental results suggest its effectiveness. The assistive electrode proposed in this study is different from those reported in literature and is prepared after initial investigative study with trial and error, as demonstrated in our previous studies and its thickness is 300 µm roughly [ 47 , 48 ].…”
Section: Methodsmentioning
confidence: 99%
“…The preparation time for the new coating was an hour and the experimental results suggest its effectiveness. The assistive electrode proposed in this study is different from those reported in literature and is prepared after initial investigative study with trial and error, as demonstrated in our previous studies and its thickness is 300 µm roughly [ 47 , 48 ].…”
Section: Methodsmentioning
confidence: 99%
“…First approach is to add secondary electrically conductive phase. However this kind of reinforcement affects mechanical properties of ceramics such as hardness, flexural strength and fracture toughness [5]. Second approach is to apply Assisting Electrode Method, where conductive coating is applied on top of insulating ceramics [6].…”
Section: Introductionmentioning
confidence: 99%
“…Second spark decomposes newly formed intrinsic conductive layer together with ceramics. Crucial aspect in maintaining s[ machining of non-conductive ceramics is formation of secondary intrinsic conductive layer and removal of this layer with ceramics [5][7] [8]. As long as this sequence is repeated steadily, machining of nonconductive ceramics is possible.…”
Section: Introductionmentioning
confidence: 99%